PENGARUH KELENGKAPAN DATA ,KETELITIAN, KECEPATAN TERHADAP KEPUASAN KONSUMEN PADA PT. FEDERAL INTERNATIONAL FINANCE (FIF) CABANG BATAM - Rafi Al Amin; Edwin Agung Wibowo (LPPM Universitas Ibnu Sina, 2021)
The purpose of this study is to determine the effect of data completeness, accuracy, speed on customer satisfaction. The method that I use in the preparation of this thesis is descriptive analysis method, namely the research method using interview techniques, observation, literature study, and data sources. Meanwhile, to analyze the data obtained, a comparison between the existing data in the field and the literature data is carried out, then an analysis is carried out to draw a conclusion. The population in this study is 8560 consumers using the Slovin formula, resulting in 99 samples. The results of this study significant regression coefficient or variable Data completeness affects the variable Customer satisfaction, the regression coefficient is significant or the Accuracy variable affects the consumer satisfaction variable, regression coefficient significant or variable speed affects the variable consumer satisfaction, And the ANOVA test results meaning that there is a linear relationship between the variable and the variable Data completeness, thorough an, Speed on Customer satisfaction.